2018
DOI: 10.1016/j.conbuildmat.2018.02.170
|View full text |Cite
|
Sign up to set email alerts
|

Ballast degradation: Effect of particle size and shape using Los Angeles Abrasion test and image analysis

Abstract: Ballast track is the most widely used track for the railway transport, and ballast bed plays a significant role to provide resistances during train operation. Generally, the ballast bed consists of crushed stones. To achieve the mitigation of ballast degradation, the first priority is to describe the degradation development and to study its effect factors. The influence of ballast morphology (particle size and shape) on ballast degradation is examined here using the Los Angeles Abrasion (LAA 1) test in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…where Δ FI and Δ MDE are the ratios of the flakiness indexes and micro-Deval test results which were made in pair, FI 1 and M DE,1 are the test results of the sample with the smaller FI value in the pair and FI 2 and M DE,2 are the test results of the sample with the higher FI value in the pair. Previous studies (Rigopoulos et al 2013;Bobály and Gálos 2016;Guo et al 2018) suggested that the shape of the particles affect aggregate properties. Bobály and Gálos (2016) Fig.…”
Section: Two-variable Analysesmentioning
confidence: 96%
See 1 more Smart Citation
“…where Δ FI and Δ MDE are the ratios of the flakiness indexes and micro-Deval test results which were made in pair, FI 1 and M DE,1 are the test results of the sample with the smaller FI value in the pair and FI 2 and M DE,2 are the test results of the sample with the higher FI value in the pair. Previous studies (Rigopoulos et al 2013;Bobály and Gálos 2016;Guo et al 2018) suggested that the shape of the particles affect aggregate properties. Bobály and Gálos (2016) Fig.…”
Section: Two-variable Analysesmentioning
confidence: 96%
“…According to the results, the flaky grains reduce the resistance to abrasion or fragmentation. Guo et al (2018) studied the effect of grain size and shape on resistance to fragmentation with image analysis. Imaging techniques were also used to measure and describe the aggregate shape properties (Profitis et al 2012(Profitis et al , 2013 or the grain size (Profitis et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3D laser scanners have been used for scanning large particles, such as ballast in pavements (e.g. [27][28][29]). Here, a 3D laser scanner is employed (LPX-60, Roland DG Corporation, Hamamatsu, Japan).…”
Section: D Laser Scanner For the Surface Texture At Large Scalesmentioning
confidence: 99%
“…Laser scanning of ballast, which can be traced to at least Tolppanen (2001), is becoming the de facto method for ballast particle scanning. Works such as (Anochie-Boateng et al, 2013;Mvelase et al, 2017) or, more recently, Guo (2018) who proposes new parameters for ballast degradation based solely on analysis of 3D digital particle models, have employed laser scanning to investigate particles from different rocks, before and after testing, with coarser and finer meshes. Paixão et al (2018) proposes a low-cost photogrammetry method that compares, in many aspects, favourably with laser scanning.…”
Section: -Introductionmentioning
confidence: 99%